The American Society of Retina Specialists 2016 Founders Award Lecture: Retinal Tumors: Understanding Clinical Features, OCT Morphology, and Therapy. (January 2017) - Shields, Carol L.; Shields, Jerry A.
Purpose: To review the current state of the art of retinal tumors with respect to clinical features, imaging, and management. Methods: Review of published literature and personal experience from an ocular oncology service. Results: There are several tumors that arise from the sensory retina including those of glial origin (astrocytic hamartoma, acquired astrocytoma, and solitary circumscribed retinal astrocytic proliferation), neural origin (retinoblastoma), and vascular origin (hemangioblastoma, cavernous hemangioma, racemose hemangioma, and vasoproliferative tumor). Most retinal tumors are benign with the exception of retinoblastoma and retinal metastasis. Some retinal tumors are associated with systemic oculoneurocutaneous syndromes such as tuberous sclerosis complex (TSC), 13q deletion syndrome, Von Hippel–Lindau disease, and systemic cavernous and racemose hemangioma syndromes with ocular, cutaneous, neurologic, and other findings. Regarding management, recent data indicate that retinal astrocytic hamartoma and retinal achromic patch are key to the diagnosis of TSC and imply greater risk for brain and kidney tumors. Some children with TSC respond to mammalian target of rapamycin inhibitors, controlling brain, kidney, and eye tumors. Children with retinoblastoma are all screened genetically, and systemic evaluation is provided for detection of metastasis and secondary-related tumors. Newer chemotherapy regimens by intravenous or intra-arterial routes have revolutionized retinoblastoma control. Retinal vascular tumors are uncommon but can have serious systemic implications. Therefore, imaging of the brain for related cerebellar hemangioblastoma, midbrain racemose hemangioma, or multifocal cavernomas is performed. Genetic testing for each disease can be revealing. Conclusions: Retinal tumors are often benign, can be recognized by clinical and imaging features, and can be associated with important systemic syndromes.